Spontaneous Regression of Hepatocellular Carcinoma and Review of Reports in the Published English Literature - Moaz B. Y. Chohan; Nick Taylor; Carla Coffin; Kelly W. Burak; Oliver F. Bathe (Case Reports in Medicine)
Background. Spontaneous regression of hepatocellular carcinoma (HCC) is a rare event, although it has been described by numerous groups. The long-term fate of individuals experiencing an SR is not well described, and the underlying mechanism(s) of SR are unknown. Case Presentation: A 79-year-old Asian female with metastatic HCC taking only valsartan for hypertension had a marked reduction in tumor dimension in the primary tumor and the pulmonary metastases. Serum alpha-fetoprotein (AFP) decreased from 17,833 μg/L to 26 μg/L. Her disease progressed after 71 months, and she died shortly after. In a review of 66 patients with SR reported in the English literature, median survival was 83 months. Median survival in 37 cases that underwent resection after SR was 108 months. Conclusions. The case and a review of the literature illustrate that SR is often durable and associated with an excellent prognosis. Understanding the underlying mechanism of SR may point to novel therapeutic strategies.